Od „topografii” do Nowej Topografii. Dwie natury ujawnione przez fotografowany krajobraz - Filanowski, Błażej (Strategie komunikacyjne i procesy twórcze, 2022)
New Topographics is an american photographers’ group whom in the 1970s referred to "topographics" - nineteenth-century photographs of the American West landscape. The "topographers" represented romantic ethos, visible in spectacular shots creating the myth and cultural identity of the colonized West also the entire United States. The New Topographics preferred repetitiveness and banality aesthetic of the contemporary landscape west of the Mississippi. Both movements are often analyzed in the context of identity changes and the demythologization of the region. In the paper, the achievements of "topographers" and the New Topographics are analyzed as visual messages representing the meaning of the current concept of nature - assuming that the concept of nature is discursive and its content changes over time.